Nigeria’s Foreign Policy, Regional Obligations and Constant Order Closures - Enyiazu, Chukwuemeka (Journal of Contemporary International Relations and Diplomacy, 2022)
Colonialism destroyed Africa’s long-standing intra-African trade. Hence, at independence there was a move for regional integration to diversify Africa’s economy. Nigeria had been at the driving seat of Africa’s regional integration. In West Africa, Nigeria pioneered the formation of the Economic Community of West African States (ECOWAS) in 1975. Though Africa has 21.2% of the global landmass and 13.7% of world population, its share of global economic activities is a meagre 2.6%. Its intratrade is 12%, paralleled to an average of 53.5% in other regions of the world. However, Nigeria over time has engaged in anti-trade policies like border closure, the latest being on 20 August 2019, three months after signing the African Continental Free Trade Agreement (AfCFTA). This has caused ripples within Nigeria, West Africa and Africa at large. This study interrogates Nigeria’s constant border closures, with questions on whether it is in Nigeria’s national interest and if its objective were achieved? The study uses the Regional Leader Role framework of analysis, a sub-set of National Role theory (NRC). The study is a qualitative and non-experimental study and is based on the single case ex-post-facto (after-the-fact) design. Documentary method of data collection is used. The study concludes that Nigeria with over 1,499 illegal land routes into the country, cannot even ‘close’ its border, hence border closure is a lose-lose policy for Nigeria and recommends collaborative actions with her neighbours, the strengthening of border and ports infrastructures as the way forward.